1991
DOI: 10.1093/ije/20.3.787
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity due to Schistosoma mansoni among Sugar-Cane Cutters in Zimbabwe

Abstract: Quantitative determination of Schistosoma mansoni infection was carried out on 1995 cane cutters of the Hippo Valley and Triangle Sugar Estates. A total of 315 cutters were chosen for the study on the basis of S. mansoni infection and lack of anti-schistosomal chemotherapy during the previous three years. Stool consistency and blood and mucus in stool were determined for all the infected cutters. Overt and occult blood in stool was detected in a significantly high number of infected people compared to the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In China, no relationship was observed between FOB and the presence or intensity of S. japonicum infection 45. In contrast, studies in Brazil and Zimbabwe showed a positive correlation between intensity of S. mansoni infection and percentage of FOB-positive stools 27,46. Similarly, in the Philippines, persons with heavy S. japonicum infections were 3.5 times more likely to be FOB positive than those with no or light to moderate infections 28.…”
Section: Discussionmentioning
confidence: 97%
“…In China, no relationship was observed between FOB and the presence or intensity of S. japonicum infection 45. In contrast, studies in Brazil and Zimbabwe showed a positive correlation between intensity of S. mansoni infection and percentage of FOB-positive stools 27,46. Similarly, in the Philippines, persons with heavy S. japonicum infections were 3.5 times more likely to be FOB positive than those with no or light to moderate infections 28.…”
Section: Discussionmentioning
confidence: 97%
“…28 In cross-sectional and case-control studies in the context of Schistosoma mansoni, investigators have found strong evidence for a relationship between fecal occult blood and intensity of schistosomiasis infection. [29][30][31] In one such study, individuals with moderateor high-intensity S. mansoni had increased prevalence of occult blood; however, uninfected individuals had a 23.1% prevalence of occult positivity, and no adjustment was made for the presence of hookworm infection, which was endemic. 30 In another study, high-versus low-intensity infection with S. mansoni increased the risk for occult positivity by approximately 4-fold.…”
Section: Discussionmentioning
confidence: 99%
“…30 In another study, high-versus low-intensity infection with S. mansoni increased the risk for occult positivity by approximately 4-fold. 31 Given the lack of control for hookworm and trichuris infections, which have been associated with occult blood loss at high intensities, 16,32 it is difficult to interpret the studies in S. mansoni. This study suggests that occult blood loss may be relevant only at high-intensity infection in S. japonicum.…”
Section: Discussionmentioning
confidence: 99%
“…Across community-based surveys worldwide, detection of intestinal blood loss in schistosomiasis-endemic areas has revealed a positive association between egg-patent infection and presence of blood in stools [7] [9] . However, the majority of these studies used guaiac-based fecal occult blood (FOB) tests that are known to be less sensitive than the FOB immunochemical assays now widely used for colorectal cancer detection [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%